Anthropogenic bottom‐up and top‐down impacts on boreal breeding waterbirds - Sari Holopainen; Kim Jaatinen; Toni Laaksonen; Andreas Lindén; Petri Nummi; Markus Piha; Hannu Pöysä; Tero Toivanen; Veli‐Matti Väänänen; Mikko Alhainen; Aleksi Lehikoinen (Ecology and Evolution, 2024)
Abstract Wetland habitats are changing under multiple anthropogenic pressures. Nutrient leakage and pollution modify physico‐chemical state of wetlands and affect the ecosystem through bottom‐up processes, while alien predators affect the ecosystems in a top‐down manner. Boreal wetlands are important breeding areas for several waterbird species, the abundances of which potentially reflect both bottom‐up and top‐down ecosystem processes. Here, we use long‐term national monitoring data gathered from c. 130 waterbird breeding sites in Finland from the 1980s to the 2020s. We hypothesised that the physico‐chemical state of the waters and increasing alien predator abundance both play a role in steering the waterbird population trends. We set out to test this hypothesis by relating population changes of 17 waterbird species to changes in water chemistry and to regional alien predator indices while allowing species‐specific effects to vary with foraging niche (dabblers, invertivore divers, piscivorous divers, herbivores), nesting site, female mass and habitat (oligotrophic, eutrophic). We found niche and nesting site‐specific, habitat‐dependent changes in waterbird numbers. While the associations with higher phosphorus levels and browning water were in overall positive at the oligotrophic lakes, the numbers of invertivore and piscivore diving ducks were most strongly negatively associated with higher phosphorus levels and browning water at the eutrophic lakes. Furthermore, increased pH levels benefitted piscivores. Invertivore diving duck species nesting on the wetlands had declined most on sites with high alien predator indices. Large herbivorous species and species preferring oligotrophic lakes seem to be successful. We conclude that the large‐scale breeding waterbird decline in Finland is closely connected to both bottom‐up and top‐down processes, where negative associations are emphasised especially at eutrophic lakes. Niche‐, nest site‐ and habitat‐specific management actions are required to conserve declining waterbird populations. Managing wetlands on catchments level together with alien predator control may provide important approaches to future wetland management.